Generation of phospho‐ubiquitin variants by orthogonal translation reveals codon skipping. Issue 10 (4th May 2016) - George, Susanna; Aguirre, Jacob D.; Spratt, Donald E.; Bi, Yumin; Jeffery, Madeline; Shaw, Gary S.; O'Donoghue, Patrick
Abstract : The activity of the Parkinson's disease‐linked E3 ligase parkin is stimulated by phosphorylation at ubiquitin Ser65 (pUb S65 ). The role of other ubiquitin phospho‐sites and their kinases are unknown. We produced pUb variants (pS7, pS12, pS20, pS57, pS65) by genetically encoding phosphoserine with the UAG codon. In release factor‐deficient Escherichia coli (ΔRF1), intended to enhance UAG read‐through, we discovered ubiquitin variants lacking the UAG‐encoded residue, demonstrating previously undocumented +3 frame shifting. We successfully purified each pUb variant from mistranslated products. While pUb S20 failed to stimulate parkin, parkin was partially active with pUb S12 . We observed significant ubiquitination when pUb S65 was the sole substrate. Abstract :